Baseline survey on functioning of abortion services in government approved CAC centres in three pilot districts of Nepal - Karki, C; Ojha, M; Rayamajhi, RT (Kathmandu University Medical Journal, 2009)
Background: Abortion has been legalized in Nepal since September 2002 and under this law, Comprehensive Abortion Care (CAC) service is being provided through listed service providers and listed health facilities from 2004. Nepal Government has prioritized the national safe abortion program and is working with many government and non government partners for providing this service. Till date medical abortion services are not made available at any of the health facility. Government is now preparing to introduce this service in six selected pilot districts. Objective: This survey was carried out to assess the functioning of existing abortion services in 12 Government approved CAC sites of three districts. Materials and methods: Direct observation of the functioning of these centers, assessment of physical facilities and service provider's skill was done. At the same time service provider's attitude and knowledge on CAC service and other abortion services were also assessed through semi structured interviews. Quality of record keeping and the feasibility of initiating the medical abortion service in these sites were also studied. Result: Number of listed centers in six pilot districts was twenty nine. Study districts have 16 listed centers. Visited sites were twelve; four managed by Government and eight by non government organizations. Thirty three thousand nine hundred and twenty women have availed this service so far: only 4.76% of them received service from Government facilities. Marie Stopes International (MSI) topped the list in providing service to the maximum number of clients (75.64%) and Family planning association of Nepal (FPAN) was the second. MSI centre was also first to initiate the service. Government facilities provide 24 hours service unlike private facilities which are open only up to 5.00 pm. Cost for the service varies from rupees 900/- to rupees 1365/- and is cheaper at Government facilities. Private sectors have separate setups and Government have allocated some space within their already existing infrastructure for CAC service. Private sectors were better in providing the information to public about the availability of service. There were total 20 trained service providers for first trimester abortion service. They are more at Government facilities. They seem to be positive to CAC service and had good knowledge and skill of service delivery. Complications were not recorded at most of the sites. Pain management and infection prevention practice needs improvement at the Government sites. All the sites had identified their referral sites and had one or the other arrangement for referral. Conclusion: CAC service has become accessible and affordable to Nepalese women even at peripheral level. CAC sites are functioning well. Initiation of medical abortion and second trimester abortion services at these sites are feasible and would expand the option and choices available. Key words: Comprehensive abortion care (CAC), medical abortion, unsafe abortion doi: 10.3126/kumj.v7i1.1762       Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 31-39